2003
DOI: 10.1128/jvi.77.7.4104-4112.2003
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A Virus-Infected Hosts Boost an Invasive Type ofStreptococcus pyogenesInfection in Mice

Abstract: The apparent worldwide resurgence of invasive Streptococcus pyogenes infection in the last two decades remains unexplained. At present, animal models in which toxic shock-like syndrome or necrotizing fasciitis is induced after S. pyogenes infection are not well developed. We demonstrate here that infection with a nonlethal dose of influenza A virus 2 days before intranasal infection with a nonlethal dose of S. pyogenes strains led to a death rate of more than 90% in mice, 10% of which showed necrotizing fascii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
97
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(106 citation statements)
references
References 39 publications
7
97
0
1
Order By: Relevance
“…It is unlikely that either the RSV-induced cytopathic effect on the epithelium or expression of viral glycoproteins or upregulation of host proteins on the cellular surface contribute to the RSV-enhanced pneumococcal bacteremia when RSV and pneumococci are inoculated simultaneously. Okamoto et al found that the direct interaction between influenza A virus and group A streptococci induced a lethal respiratory infection in a murine model (23,24). Similar findings with respect to a lethal synergism between influenza virus and pneumococci were obtained by Mc.…”
Section: Discussionsupporting
confidence: 66%
“…It is unlikely that either the RSV-induced cytopathic effect on the epithelium or expression of viral glycoproteins or upregulation of host proteins on the cellular surface contribute to the RSV-enhanced pneumococcal bacteremia when RSV and pneumococci are inoculated simultaneously. Okamoto et al found that the direct interaction between influenza A virus and group A streptococci induced a lethal respiratory infection in a murine model (23,24). Similar findings with respect to a lethal synergism between influenza virus and pneumococci were obtained by Mc.…”
Section: Discussionsupporting
confidence: 66%
“…The RSV attachment glycoprotein (G) protein, present on the surface of either RSV virions or infected cells, can serve as a binding structure for non-typeable H. influenzae (Avadhanula et al, 2007), S. pneumoniae (Avadhanula et al, 2007;Hament et al, 2005) and Pseudomonas aeruginosa (Van Ewijk et al, 2007). Similarly, integration of influenza virus haemagglutinin into the cell membrane of infected cells facilitates attachment and invasive disease of group A streptococci in mice (Okamoto et al, 2003). On top of this, the binding of fibrinogen to cells infected with influenza A, and the modulation of several surface molecules in influenzainfected cells is thought to aid the binding and invasion of group A streptococci (Hafez et al, 2010;Sanford et al, 1982).…”
Section: Receptor Expressionmentioning
confidence: 99%
“…Though RV infection is notable for the lack of cytotoxicity relative to other respiratory viruses, such as RSV and influenza (14,30,31), RV has been shown to induce apoptosis by activating caspase 3 and caspase 9 and poly(ADP-ribose) polymerase activation in nonpolarized airway epithelial cells (32). To examine whether RV causes apoptosis in primary airway epithelial cells differentiated into mucociliary phenotype and in polarized 16HBE14o-cells, we infected these cultures with RV39 (MOI of 1) or sham, as described above, and determined the population of apoptotic cells by staining with annexin V and propidium iodide followed by flow cytometric analysis.…”
Section: Apoptosis Does Not Contribute To Rv-induced Reductions In R Tmentioning
confidence: 99%